Durian Seed Cake As A Solution For Using Durian Seed Waste - Ainun Habibah; Yunita Yunita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2019)
KEJITAN (Kue Biji Durian or Durian Seed Cake) is a processed cake made from durian seed flour. The high production of durian fruit in NTB is not balanced with the use of good durian seeds and only becomes waste. Therefore, KEJITAN (Durian Seed Cake) is made as a solution to maximize the utilization of healthy durian seeds and high selling value. The step taken is a raw material survey, which is a survey related to the availability of raw materials for making durian seed flour. Then, a survey is carried out related to products that are sold in the market and are in demand by consumers. Then after the production phase, marketing of KEJITAN products is carried out through mass media such as Instagram, Whatsapp and direct sales to consumers around the city of Mataram. Publications through online mass media aim to introduce KEJITAN products to all groups, seeing social media users from all walks of life. The output produced by the KEJITAN business is the realization of a business in the form of processed products made from durian seed flour which has not been touched by its existence and has health and economic benefits, fostering a love for consuming processed products made from waste.Keywords: Durian, waste, flour